Role of TLR-2 and fungal surface antigens on innate immune response against Sporothrix schenckii - Negrini, Thais de C. [UNESP]; Ferreira, Lucas S. [UNESP]; Alegranci, Pâmela [UNESP]; Arthur, Rodrigo A.; Sundfeld, Pedro P. [UNESP]; Maia, Danielle C. G. [UNESP]; Spolidório, Luis Carlos [UNESP]; Carlos, Iracilda Z. [UNESP] (Taylor & Francis, 2013)
Sporotrichosis is an infection caused by the dimorphic fungus Sporothrix schenckii. Toll-like receptors (TLRs) play an important role in immunity, since they bind to pathogen surface antigens and initiate the immune response. However, little is known about the role of TLR-2 and fungal surface antigens in the recognition of S. schenckii and in the subsequent immune response. This study aimed to evaluate the involvement of TLR-2 and fungal surface soluble (SolAg) and lipidic (LipAg) antigens in phagocytosis of S. schenckii and production of immune mediators by macrophages obtained from WT and TLR-2 -/- animals. The results showed that TLR-2-/- animals had had statistical lower percentage of macrophages with internalized yeasts compared to WT. SolAg and LipAg impaired phagocytosis and immunological mediator production for both WT and TLR-2-/-. The absence of TLR-2 led to lower production of the cytokines TNF, IL-1β, IL-12 and IL-10 compared to WT animals. These results suggest a new insight in relation to how the immune system, through TLR-2, recognizes and induces the production of mediators in response to the fungus S. schenckii. Copyright © Informa Healthcare USA, Inc.
Keywords: Cytokines; Macrophages; Mice; Phagocytosis; Sporothrix schenckii; TLR-2; fungal lipidic antigen; fungal surface soluble antigen; fungus antigen; interleukin 10; interleukin 12; interleukin 1beta; toll like receptor 2; tumor necrosis factor alpha; unclassified drug; animal experiment; controlled study; cytokine production; female; innate immunity; macrophage; mouse; nonhuman; phagocytosis; priority journal; Animals; Antigens, Fungal; Cells, Cultured; Female; Immunity, Innate; Inflammation Mediators; Mice, Inbred C57BL; Mice, Knockout; Sporothrix; Sporotrichosis; Toll-Like Receptor 2